Dampak Kebijakan Pengadaan Obat Pada Puskesmas di Jakarta Era Jaminan Kesehatan Nasional - Sulistiyono, Hari; Sarnianto, Prih; Anggiani, Yusi (Window of Health : Jurnal Kesehatan, 2020)
Medicine is an important input in health services. If the medicine is not available, it can negatively affect the patient's therapeutic results. The purpose of this observational study is to find out the process of drug procurement at the primary health care, in Jakarta, which are all of have Public Service Agency status, in order to map out the problem and its solution. Primary data were obtained through in-depth interviews and focus group discussion with Pharmacists and Commitment Officers from 20 primary health care representing 5 municipalities, plus 1 of thousand islands primary health care, using 20 types of indicator drugs, 4 of them are antihypertensive drugs. The results of the study that conducted in January to March 2019 showed that of 21 primary health care conducting e-Purchasing, 11 primary health care succeeded, 3 primary health care failed but followed up through direct procurement, and 10 other primary health care failed without following up, resulting in an antihypertensive drug shortages. The primary health care that succeed e-Purchasing, were found to have pharmacists in charge of drug procurement. In primary health care, where there is a drug shortages, existing pharmacists are not given a role in the procurement of drugs, this right has an impact on the average proportion of hypertension referral patients reaching 12%, or 4 times that of puskesmas fulfilling drug needs, which is 3%. It can be concluded that the implementation of JKN medicine procurement in primary health cares in Jakarta is still experiencing obstacles, which requires the support of BLUD procurement regulations and the role of pharmacists in drug procurement.